X‐ray characterization of self‐standing bent Si crystal plates for Large Hadron Collider beam extraction. Issue 2 (30th March 2020) - Camattari, Riccardo; Romagnoni, Marco; Bandiera, Laura; Bagli, Enrico; Mazzolari, Andrea; Sytov, Alexei; Haaga, Simon; Kabukcuoglu, Merve; Bode, Simon; Hänschke, Daniel; Danilewsky, Andreas; Baumbach, Tilo; et al.
Abstract : Two perfect silicon mono‐crystals were bent to be used to deflect high‐energy charged particle beams in the context of beam extraction and/or beam collimation at accelerator facilities, such as for steering the 7 TeV proton beam of the Large Hadron Collider. The sample curvature and quality were tested at the ID11 beamline of the European Synchrotron Radiation Facility via hard X‐ray diffraction and at the Karlsruhe Institute of Technology synchrotron via X‐ray white‐beam topography. Abstract : Bent crystals can be used to deflect high‐energy charged particles for beam extraction and/or beam collimation at accelerator facilities, thanks to the channelling phenomenon. In the present paper, two perfect silicon mono‐crystals were bent using two different methods: sandblasting and the application of a carbon fibre composite. In particular, these samples were obtained for the realization of bent crystal prototypes to be used to steer the 7 TeV proton beam of the Large Hadron Collider in the context of the CRYSBEAM project. The two bending methods were selected since they allow a very homogeneous curvature of the crystals to be obtained, which is essential for high channelling efficiency. Moreover, the deformation obtained is self‐standing, i.e. there is no need for any external device to keep the samples bent. Self‐standing curvature can be useful because the presence of an external bender could be a severe limitation in the collider beam‐pipe. The curvature of the samples was measured through high‐energy X‐ray diffraction at the ID11 beamline of the European Synchrotron Radiation Facility in Grenoble, France. Since the diffraction efficiencies obtained were in good agreement with theoretical expectations, it follows that the manufacturing techniques did not damage the samples, i.e. the crystallographic quality was preserved. Finally, the crystal quality of the sandblasted sample was investigated in detail at the synchrotron source at Karlsruhe Institute of Technology by X‐ray white‐beam topography. The measurements showed no diffusion of defects from the machined surfaces to the crystal bulk.